THE INFLUENCE OF COMPENSATION AND TRAINING ON ORGANIZATIONAL PERFORMANCE THROUGH THE DISCIPLINE OF PT X - Marinda, Vina S.; Nur'Raihan, Widya Luthfi; Anari, Diana; Merdikania, Rita; Ramadhan, Dani Ali; Sidik, Rizki Permana (CENTRAL ASIA AND THE CAUCASUS, 2022)
Human resources are the driving factors of the company to achieve the goals, so the company’s efforts in encouraging its employees to work better must continue to be carried out and maintained. The employees whose carrying out their responsibilities and tasks assigned to them is needed by company to achieve organizational performance. The purpose of this research is to explain how the effect of training and compensation on organizational performance through discipline at PT X. This research is an explanatory research with the aim of explaining the correlation between the variables studied and giving an influence on the research hypothesis. And using a quantitative and qualitative approach with 75 employee respondents at PT X and path analysis calculations. The data used in this research are primary and secondary data. The descriptive data processing’s result shows that training, compensation and discipline at PT X has very good quality, and organizational performance has good quality. The Inference data processing’ result, that training and compensation have no significant effect on organizational performance through work discipline. Although directly compensation has a significant effect on work discipline and training has a significant effect on organizational performance. However, training has no significant effect on discipline, compensation has no significant effect on organizational performance, and work discipline also has no significant effect.